Evaluation of Metanephrine and Lactate Dehydrogenase in Pediatric Wilms Tumor and Neuroblastom - Jwda, Nihad A.; Rasheed , Manal K.; H.Ghali , Hasanein (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Wilms’ tumor and Neuroblastoma are common pediatric malignancies, with biochemical markers like plasma metanephrines and serum lactate dehydrogenase (LDH) being studied for diagnostic and prognostic values. Metanephrine, a catecholamine metabolite, is elevated in Neuroblastoma due to tumor secretion. Elevated LDH levels may correlate with tumor burden and indirectly indicate disease activity. Objectives: To evaluate plasma metanephrine and lactate dehydrogenase as biomarkers in Neuroblastoma and Wilms tumor in pediatric patients. Methods: The study was conducted between February and December 2024, in the Children Welfare Teaching Hospital, Medical City Complex, Baghdad, Iraq, and the Department of Biochemistry, College of Medicine, University of Baghdad. A Total of 98 children under the age of 10 years were included and grouped into: Group 1: 34 patients with Neuroblastoma, Group 2: 31 patients with Wilms tumor, and Group 3: 33 healthy children serving as controls. Blood samples (5 mL) were collected from all participants. Plasma metanephrine levels were measured using an ELISA method, while lactate dehydrogenase levels were determined using the Roche Cobas analyzer. Anthropometric parameters were also measured. Results: The study found no significant differences in age, weight, or height among Neuroblastoma, Wilms tumor, and control groups. However, Neuroblastoma patients showed significantly higher Metanephrine levels (26.2 ± 2.24 ng/mL) compared to Wilms tumor (8.0 ± 0.28 ng/mL) and controls (7.5 ± 0.29 ng/mL) . Similarly, LDH levels were elevated in Neuroblastoma (848.8 ± 87.57 U/L) and Wilms tumor (629.3 ± 66.99 U/L) versus controls (68.6 ± 3.90 U/L), with Neuroblastoma exhibiting higher LDH than Wilms tumor. Conclusion: The study emphasizes the importance of using metanephrine measurements for Neuroblastoma diagnosis and monitoring, as these metabolites can inform treatment response and disease progression. Neuroblastoma exhibits higher levels of metanephrine and lactate dehydrogenase, indicating a larger tumor burden. Wilms tumor does not share these characteristics.